How to clean up the Ganges? - Shah, Tushaar; Ray, Chittaranjan; Lele, Ume (American Association for the Advancement of Science, 2018)
For millennia, the Ganges River, holy to Hindus, has provided livelihoods, food, and water for Nepal, India, and Bangladesh. Last month, one of India's leading environmental activists died after a 111-day hunger strike, failing to evoke changes to save India's most revered river (known as Ganga). After years of unrelenting abuse, Ganga is now one of the world's worst polluted rivers. India's Prime Minister Narendra Modi vowed in 2014 to clean Ganga by 2019, but despite increased funding and much lip service, the river is more polluted than before. Mr. Modi needs a new strategy.